Ice cream bear - Alborough, Jez (New York : Scholastic Inc, 1989)
Bear like ice cream a lot! So when a marvelous miracle happens and ice cream snow begins to fall from the sky, it's a dream come true. Or is it?
Keywords: Bears-Fiction; Ice creams-Fiction